Out of the Ashes and Into the Dust: Britain’s Developmental State (World Marxist Review, 2026)
Among the various striking aspects of Cheng Enfu's published work are a consistent reiteration of the variegated nature of economic development in history, and the failure of one-size-fits-all Western teleologies in practice. Despite this, acknowledgement of the historical reality must be persistently restated in the refutation of those teleologies, supported as they are by a monolithic belief system that demands of its adherents a heroic tolerance of cognitive dissonance, and a rendering of the historical record of such violence to the facts as to extinguish enormous swathes of human experience (and indeed sometimes the humans who embodied that experience). At the same time as performing this sadly necessary defensive intellectual work, Cheng opens up to the reader a window on the purposive, nation-focused orientation of China's economic policymakers, as they steer the country's economic development towards the goal of common prosperity. While the challenges facing that country are undoubtedly of such complexity and magnitude as to demand an appropriate humility, there is, nevertheless, a clear strategic focus combined with a strong alertness to possibility, supported by a consciously adaptive rationality willing to learn from experience, whether Chinese or foreign. The lynchpin is a functional and competent state apparatus of a kind increasingly alien to the residents of countries typically regarded as paragons of policy virtue, with membership of the Organisation for Economic Cooperation and Development (OECD) as the status-enhancing imprimatur of success (Davis 2016).